Characteristics and outcomes of re‐do percutaneous paravalvular leak closure. Issue 4 (10th February 2017) - Al‐Hijji, Mohammed A.; Alkhouli, Mohamad; Sarraf, Mohammad; Zack, Chad J.; Malouf, Joseph F.; Nkomo, Vuyisile T.; Cabalka, Allison K.; Reeder, Guy S.; Rihal, Charanjit S.; Eleid, Mackram F.
Abstract : Background: Percutaneous paravalvular leak (PVL) closure is an alternative treatment option for severely symptomatic, high‐surgical risk patients with PVL. Some patients require multiple percutaneous PVL closure procedures. However, the procedural characteristics and success rate of re‐do PVL closure have not been well studied. Aims: The aim of this study is to investigate the indications, procedural characteristics, technical success rate, and 30‐day major adverse cardiovascular events (MACE) in patients who underwent re‐do PVL closure. Methods: Consecutive patients who underwent percutaneous paramitral or paraaortic leak closure at Mayo Clinic, Rochester, Minnesota from 2004 through 2015 were studied. Clinical and procedural characteristics of patients who underwent re‐do PVL closure were compared to age‐ and sex‐matched patients who underwent their first percutaneous PVL closure. Procedure success and 30‐day MACE were compared in both the groups. Results: Among 223 identified percutaneous PVL closures, 16 (7%) were re‐do procedures. Patients who underwent re‐do PVL closure were predominantly men (87.5%) with a mean age of 68 ± 15 years and an estimated mean Society of Thoracic Surgery (STS) 30‐day mortality of 4.6 ± 2.8. Half of the re‐do PVL closures were performed on mechanical valves and 62.5% were performed on paramitral defects. Indications for re‐do PVL closure were: (1) emergence of new significant paravalvular defects in 50%, (2) incomplete index defect closure in 43.75%, and (3) index procedural complication in 6.25% of the cases. Procedural success was 75% in re‐do procedures vs. 85.4% in age‐ and sex‐matched control group ( P  = 0.45). Thirty‐day MACE was 12.5% in the re‐do group compared to 4.2% in the age‐ and‐sex matched patients who underwent PVL closure for the first time ( P  = 0.35). Conclusion: Re‐do percutaneous PVL closure is feasible with favorable procedural success rate and low 30‐day MACE. Development of new paravalvular defects is the most common indication for re‐do PVL closure, highlighting the importance of careful longitudinal monitoring and follow‐up. © 2017 Wiley Periodicals, Inc.